PROFIL KONSEP DIRI PESERTA DIDIK KELAS VIII A DI SMPN 3 BALEENDAH KABUPATEN BANDUNG - Sari Dharshany; Wikanengsih Wikanengsih; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The purpose of this study was to determine the self-concept profile of class VIII students so that it could be seen the number of students who had a positive self-concept and the number of students who had a negative self-concept.  Self-concept is a relationship between attitudes and beliefs about ourselves. Self-concept is an ongoing process along with individual growth and development. The method used in this research is descriptive quantitative method.  The research sample was 32 students of class VIII A SMPN 3 Baleendah.  The technique of collecting data is by distributing self-concept questionnaires.  Based on the results of distributing self-concept questionnaires, it can be concluded that students who have a positive self-concept are in the low category of 4 people, 24 people in the medium category and 4 people in the high category.Keywords: : Self-concept, students, developmental tasks